2008
DOI: 10.1007/s00134-008-1060-5
|View full text |Cite
|
Sign up to set email alerts
|

Dose-response effects of milrinone on hemodynamics of newborn pigs with hypoxia-reoxygenation

Abstract: When used to treat shock in newborn piglets with hypoxia-reoxygenation, milrinone improved cardiac output and carotid flow while maintaining systemic blood pressure. Pulmonary hypertension was not aggravated. Further studies are needed to confirm these findings in asphyxiated neonates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…Milrinone, a phosphodiesterase (PDE)‐3 inhibitor, is an inotrope and vasodilator, increasing cellular cAMP and improving hypoxic pulmonary haemodynamics (Joynt et al ., 2008; Lakshminrusimha et al ., 2009). Studies on the functional effects of milrinone have recently focused on prostanoid receptors, as milrinone attenuates inflammatory lung injury (Bueltmann et al ., 2009), potentiates the anti‐remodelling effect of PGI 2 on hypoxic artery (Phillips et al ., 2005) and enhances relaxation to PGI 2 in PPHN (Lakshminrusimha et al ., 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Milrinone, a phosphodiesterase (PDE)‐3 inhibitor, is an inotrope and vasodilator, increasing cellular cAMP and improving hypoxic pulmonary haemodynamics (Joynt et al ., 2008; Lakshminrusimha et al ., 2009). Studies on the functional effects of milrinone have recently focused on prostanoid receptors, as milrinone attenuates inflammatory lung injury (Bueltmann et al ., 2009), potentiates the anti‐remodelling effect of PGI 2 on hypoxic artery (Phillips et al ., 2005) and enhances relaxation to PGI 2 in PPHN (Lakshminrusimha et al ., 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The changes in mesenteric blood flow are related to the changes in regional vascular resistance, and at least in part to the concomitant changes in the cardiac output. The dose-dependent effect of milrinone on cardiac output in this study has been recently reported (18). The relationship between blood pressure, cardiac output, and intestinal perfusion during H-R is still not well defined (7,8,23,24).…”
Section: Discussionmentioning
confidence: 88%
“…Stability was defined as a hemodynamic measurement change T less than 10% over 20 min, pH 7.35 to 7.45, PaO 2 of 60 to 100 mmHg, and PaCO 2 of 35 to 45 mmHg. Normocapnic alveolar hypoxia was initiated with the inhalation of a mixture of oxygen and nitrogen gas to obtain an inspired oxygen concentration of 0.10 to 0.15 and PaO 2 of 20 to 40 mmHg for 2 h. Previous studies have determined that this degree of hypoxemia in this piglet model will produce a clinical asphyxia with severe metabolic acidosis, systemic hypotension, and a decrease in pulmonary blood flow to 40% of baseline (17,18). Piglets were then reoxygenated with 100% oxygen for 1 h and a further 3 h of 21% oxygen.…”
Section: H-r and Treatment Proceduresmentioning
confidence: 99%
“…The experimentation has been previously described [8,21] . Briefly, inhalational anesthesia was used initially using isoflurane, which was substituted by a combination of intravenous midazolam (0.1-0.2 mg/kg/h) for sedation and fentanyl (5-50 g/ kg/h) for analgesia after vascular access was established.…”
Section: Anesthesia and Surgical Instrumentationmentioning
confidence: 99%
“…At 2 h of reoxygenation, when low cardiac output and hypotension predictably developed [8,21] , the piglets received either placebo (D 5 W) or levosimendan as a bolus over 10 min followed by continuous infusion at the corresponding dosage for a total of 2 h of treatment.…”
Section: H-r and Treatmentmentioning
confidence: 99%